Evaluation of an NLP-Based Chatbot for Informational Support in Bronchopulmonary Dysplasia (BPD) in neonates - Silva, Anna Beatriz; Rodrigues, Cleyton Mario de Oliveira; Endo, Patricia Takako (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2025: Anais do XVI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2025.37841, 2025)
Bronchopulmonary Dysplasia (BPD) is a chronic lung condition that affects neonates, especially those born prematurely. Despite its relevance, the lack of accessible and up-to-date information hampers the proper management of this condition for both families and healthcare professionals. This study proposes the development of a chatbot based on Natural Language Processing (NLP) technique, named Soprinho IA, to provide informational and empathetic support to both mothers and healthcare professionals, focusing on BPD information. The methodology involves data collection from various sources, text preprocessing, and training of three different NLP architectures, such as Recurrent Neural Networks (RNNs), transformers, and other state-of-the-art approaches. The Sentence-Transformer model, based on BERT, achieved the best results, with high accuracy and semantic relevance. The chatbot is integrated into a responsive web interface, offering multimodal interaction features, including audio support. The evaluation of the models demonstrated the chatbot’s effectiveness in providing contextualized and easily understandable responses, with potential to improve communication and the management of neonates with BPD. The study also highlights limitations, such as the need to improve speech-to-text conversion, and suggests future directions for the integration of AI models to support clinical decision-making.